Importance of Zinc Nanoparticles for the Intestinal Microbiome of Weaned Piglets - Baholet, Daria; Skalickova, Sylvie; Batik, Andrej; Malyugina, Svetlana; Skladanka, Jiri; Horky, Pavel (Frontiers in Veterinary Science, 2022)
Recently, we are experiencing a great boom of nanotechnology in agriculture. Currently, the scientific community is paying attention to the replacement of antibiotics and medication doses of zinc in weaned piglets. Since 2022, the use of medical doses of zinc has been banned in the European Union. Thus, pig farmers are looking for different solutions to solve these restrictions. Zinc nanoparticles appear to be an interesting alternative. These are substances which, because of their large surface area, are characterized by higher efficiency. Some studies suggest that they could have an antimicrobial effect at lower doses in weaned piglets. Zinc nanoparticles are effective against pathogenic E. Coli and can also support some positive bacterial strains. Further research should further address toxicity, the fate of nanoparticles in the environment, and the safety of the final consumer. The review provides a comprehensive overview of the use of zinc nanoparticles and their effect on the intestinal microbiome of weaned piglets.